Modulation of Brain Activity and Functional Connectivity by Acupuncture Combined With Donepezil on Mild-to-Moderate Alzheimer's Disease: A Neuroimaging Pilot Study - Zhan, Yijun; Fu, Qinhui; Pei, Jian; Fan, Mingxia; Yu, Qiurong; Guo, Miao; Zhou, Houguang; Wang, Tao; Wang, Liaoyao; Chen, Yaoxin (Frontiers in Neurology, 2022)
Background: Functional magnetic resonance imaging (fMRI) have been proven as potential pathophysiological targets in early-stage AD. Current longitudinal neuroimaging studies of AD treated by acupuncture have neither adopted comprehensive acupuncture protocols, nor explored the changes after a complete treatment duration. Thus the mechanisms of acupuncture effects remain not fully investigated. Objective: This study aimed to investigate the changes of spontaneous brain activity and functional connectivity and provide evidence for central mechanism of a 12-week acupuncture program on mild-to-moderate AD. Methods: Forty-four patients with mild-to-moderate AD and twenty-two matched healthy subjects were enrolled in this study. The forty-four AD patients received a 12-week intervention of either acupuncture combined with donepezil (the treatment group) or donepezil alone (the control group). The two groups received fMRI scans before and after treatment. The healthy subjects group underwent no intervention and received only one fMRI scan. The fractional amplitude of low frequency fluctuation (fALFF) and functional connectivity (FC) were applied to analyze the imaging data. The correlations between the imaging indicators and the changed score of Alzheimer's Disease Assessment Scale-cognitive section (ADAS-cog) were also explored. Results: After the 12-week intervention, compared to those in the control group, AD patients in the treatment group scored significantly lower on ADAS-cog value. Moreover, compared to healthy subjects, the areas where the fALFF value decreased in AD patients were mainly located in the right inferior temporal gyrus, middle/inferior frontal gyrus, middle occipital gyrus, left precuneus, bilateral superior temporal gyrus. Compared with the control group, the right precuneus demonstrated the greatest changed value of fALFF after the intervention in the treatment group. The difference of ADAS-cog after interventions was positively correlated with the difference of fALFF value in the left temporal lobe. Right-precuneus-based FC analysis showed that the altered FC by the treatment group compared to the control group was mainly located in the bilateral middle temporal gyrus. Conclusions: The study revealed the key role of precuneus in the effect of the combination of acupuncture and donepezil on mild-to-moderate AD for cognitive function, as well as its connection with middle temporal gyrus, which provided a potential treating target for AD.